Parents' Views of Schools' Involvement Efforts. (October 2014) - Rodriguez, Raymond J.; Blatz, Erin T.; Elbaum, Batya
Individual and focus group interviews were conducted with 96 parents of students with disabilities in 18 schools to explore parents' views of schools' efforts to engage them in their child's education. A mixed-methods approach was used to identify and evaluate the relative importance of eight themes related to schools' efforts to facilitate parent involvement and parents' involvement with their child at school. The results suggest important relationships among parents' initiative to become involved, their perceptions of the quality of services provided to their child, and their views of schools' efforts to facilitate their involvement. Implications for best practices and future research are discussed.